Utilization Of Organic Fertilizer Compost Made From Purple Sweet Potato Waste (Ipomoea Batatas L.) To Increase The Production Of Pakchoy (Brassica Chinensis L.) - Sheila Dwi Shilviana; Ni Luh Suriani; I Ketut Sundra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Compost is an organic fertilizer made from recycled organic materials. Fertilizers can be made from organic waste or unused organic waste. Purple sweet potato waste can be reused into compost. The purpose of this study was to examine the effectiveness of purple sweet potato waste compost inoculated with Trichoderma harzianum in increasing the production of pakchoi and to determine the treatment of purple sweet potato waste compost to increase the production of pakchoi. The research method used is the experimental method. The experimental design used was RBD (Randomized Block Design) with 1 factor. The experiment consisted of 4 treatments of purple sweet potato compost 25 (B) g, 50 g (C), 75 g (D), 150 g (E), and 1 control (A), and was repeated 5 times. The data analysis technique used analysis of variance (ANOVA). Parameters observed were the number of leaves, plant height, leaf width, plant wet weight, plant dry weight, and root length. The results showed that the application of purple sweet potato compost affected increasing the growth and production of pakchoi. The right treatment in increasing the growth of pakchoi is treatment E. This treatment can increase the number of leaves (13.13), plant height (16.32 cm), leaf width (4.88 cm), wet weight (16.60 g), dry weight (6.35 g), and root length (15.80 cm).